2022
DOI: 10.3892/etm.2022.11153
|View full text |Cite
|
Sign up to set email alerts
|

Study on the value of antibiotic‑resistant gene detection in Helicobacter pylori in China

Abstract: The aim of the present study was to explore the value of detecting antibiotic-resistant genes in Helicobacter pylori (H. pylori) and the association between genotype and antibiotic resistance. Two gastric mucosa samples from each H. pylori-positive patient were collected. Each patient's H. pylori sample was cultured in vitro, and the agar plate dilution method was conducted. In addition, all patient samples were analyzed for the detection of antibiotic resistance-related mutant genes and VacA gene genotypes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This result is not in agreement with Agudo et al, who reported that clarithromycin resistance in H. pylori isolates was strongly associated with the vacA s2/m2 genotype; however, no association with 23S rRNA gene mutations and vacA/cagA genotypes is reported [ 21 ]. Otherwise, different studies have not found an association between vacA genotypes and antibiotic resistance [ 57 , 58 ]. Therefore, multicenter studies are needed to study the relationship between clarithromycin resistance-associated mutations and vacA/cagA genotypes of H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…This result is not in agreement with Agudo et al, who reported that clarithromycin resistance in H. pylori isolates was strongly associated with the vacA s2/m2 genotype; however, no association with 23S rRNA gene mutations and vacA/cagA genotypes is reported [ 21 ]. Otherwise, different studies have not found an association between vacA genotypes and antibiotic resistance [ 57 , 58 ]. Therefore, multicenter studies are needed to study the relationship between clarithromycin resistance-associated mutations and vacA/cagA genotypes of H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori has strict oxygen requirements. The optimal oxygen concentration range in air is 5 to 8% ( Dai et al, 2022 ), which is equal to 1.7 to 2.0 mg/L in aqueous solutions at 37°C. When the oxygen concentration in the environment is outside this range, H. pylori cannot survive.…”
Section: New Approachesmentioning
confidence: 99%
“…Vianna et al, (2018) identified seven mutation in 23s rRNA region related to antibiotic resistance, whereas the results of Jabar & Alfaisal, (2017) documented no mutations were observed in the codons but the sequencing analysis detect point mutations in exons (17,18). In a study by Dai et al, (2022) which enrolled a total of 133 H. pylori positive patients they reported that no significant link was detected between VacA genotypes patients and antibiotic resistance (19). Aziz et al, (2022) detect a number of specific virulence proteins in gastric biopsies of gastroduodenal disease H. pylori infected individuals, these proteins were controlled by CagA pathogenicity island (20).…”
Section: Dna Sequencingmentioning
confidence: 99%